Peran Kader Posyandu dalam Menurunkan Stunting di Desa Taebesa Kecamatan Amanuban Tengah Kabupaten TTS - Sophia Delaya Ku; Sirait, Rina Waty; Sinaga, Masrida; Fransiskus G. Mado (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Cadres are the main drivers in activities at the posyandu because the existence of child nutrition problems in an area is influenced by the role of posyandu cadres. This study uses a descriptive qualitative method. The informants of this study were 12 people with purposive sampling techniques. Data collection techniques through in-depth interviews and document studies. Data analysis uses the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the role of posyandu cadres in Taebesa Village at the first table in the registration stage has been done well. However, at the second table in the anthropometric measurement stage, it is not optimal because the availability of facilities and infrastructure is insufficient. At the third table, namely filling in the KMS, the role of cadres has not been carried out optimally because only a few cadres can use the table correctly. The fourth table, namely the counseling stage, has also not been carried out optimally. The cadres did not conduct counseling to mothers of toddlers. The fifth table, namely health services, is dedicated to health workers. The cadres are tasked with helping existing services. Overall, the role of posyandu cadres in Taebesa Village is still not optimal. There is a need to improve the ability of cadres in filling KMS and implementing counseling. The availability of facilities and infrastructure must also be improved to support the performance of posyandu cadres.